2022
DOI: 10.1080/01446193.2022.2053998
|View full text |Cite
|
Sign up to set email alerts
|

How transactional and transformational safety leadership behaviours are demonstrated within the construction industry

Abstract: Transactional and transformational safety leadership have been repeatedly found to be important for safety. Yet how transactional and transformational leadership behaviours are most effectively demonstrated can be dependent on the context and industry. Using an ethnographic approach, supervisor safety leadership was explored across eleven construction sites in Australia. The findings revealed that, within the construction site context, contingent reward, idealised influence, and management-by-exception behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Construction workers usually move from project to project and may work with different main contractors, but they often work in a workgroups for a relatively long period. Therefore, compared with supervisors from the main contractor, workgroup supervisors usually have a bigger influence on construction workers [32]. This paper focuses on four phenomena at the workgroup level, i.e., supervisors' transformational leadership and contingent reward behavior (one aspect of their transactional leadership), leader-member exchange, and team-member exchange.…”
Section: Group Level Factorsmentioning
confidence: 99%
“…Construction workers usually move from project to project and may work with different main contractors, but they often work in a workgroups for a relatively long period. Therefore, compared with supervisors from the main contractor, workgroup supervisors usually have a bigger influence on construction workers [32]. This paper focuses on four phenomena at the workgroup level, i.e., supervisors' transformational leadership and contingent reward behavior (one aspect of their transactional leadership), leader-member exchange, and team-member exchange.…”
Section: Group Level Factorsmentioning
confidence: 99%
“…Leadership refers to achieving the collective objectives to influence followers' behavior through a series of influencing approaches, such as making rules and providing guidance and emotional stimulation (Robbins et al, 2010). Studies have repeatedly demonstrated that leadership is important for safety (Oswald et al, 2022). Bass (1985) originally classified leadership as TfL or TsL.…”
Section: Leadership Behaviormentioning
confidence: 99%
“…, 2010). Studies have repeatedly demonstrated that leadership is important for safety (Oswald et al., 2022). Bass (1985) originally classified leadership as TfL or TsL.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Construction sites are inherently hazardous environments, characterized by a multitude of potential risks ranging from falls and equipment malfunctions to structural failures [2,3]. Despite intensive efforts to enhance safety protocols and regulations, the Sustainability 2024, 16, 5103 2 of 20 industry continues to cope with high rates of accidents and fatalities [4,5]. While technological advancements and regulatory frameworks play crucial roles in addressing safety concerns, the influence of cultural norms and socio-economic factors cannot be overstated.…”
Section: Introductionmentioning
confidence: 99%
“…Feng et al [15] explored the role of resilient culture in mitigating these challenges, emphasizing the importance of equipping workers with the skills to navigate cultural diversity effectively in safety-critical situations. Oswald et al [16] have highlighted the importance of leadership empowerment in creating an environment where workers feel empowered to voice safety concerns and actively contribute to safety improvement efforts. Hierarchical structures within construction organizations also shape safety practices and attitudes [17].…”
Section: Introductionmentioning
confidence: 99%